Diversity in Escherichia coli O157:h7 between human and bovine strains - Page, Jennifer Anne (Kansas State University, 2009)
Within the United States, it has been estimated that 60 deaths and 73,000 illnesses are caused by Escherichia coli O157:H7 infection annually (Gavin et al., 2004). Multiple effects have been known to occur with the onset of infection from E. coli O157:H7 in which some of these can become life-threatening. Escherichia coli O157:H7 is defined as a Shiga-toxin-producing E. coli strain (STEC). This microbial pathogen is a gram-negative bacillus organism that is motile, non-sorbitol fermenting, and β-glucuronidase negative. The infectious dose of E. coli O157:H7 can be as low as ten cells (Food and Drug Administration, 2009). Consumption of contaminated food, mainly undercooked ground beef and non or incorrectly pasteurized milk, are the primary sources of E. coli O157:H7 infection in human. Cattle, in particular, are considered chief asymptomatic reservoirs for this pathogen. Carried in their gut, feces, and milk, cattle carry this Shiga toxin-producing E. coli in ranges from 10[superscript]2 to 10[superscript]5 CFU/g. Although colonized with E. coli O157:H7, cattle and other ruminants show no adverse side effects from the pathogenic bacteria. There is also a difference in the prevalence of this pathogen between human and cattle. There has been a low incidence of illness caused by E. coli O157:H7 in humans when compared to the high prevalence of E. coli 057:H7 found in cattle and their environment. It has been discovered, through population genetic analysis, that E. coli O157:H7 and other O157:H- isolates make up a clone complex. In spite of the clonal nature of E. coli O157:H7 and other O157:H[superscript]- isolates, there are significant characteristics showing variability between the clone complex. These variability aspects can possibly account for the rapid divergence of E. coli strains including the recently discovered divergence of E. coli O157:H7 in to two separate lineages. Other possible reasons for a non-linear relationship between cattle prevalence and human infection include diversity of the Shiga Toxin-Encoding bacteriophage and receptors in cattle verses human, and finally the difference between the production of Locus of Enterocyte Effacement (LEE) in both human and cattle lineages.
Keywords: Escherichia coli; O157:H7; Shiga toxin; Q933; Diverse E. coli strains; Cattle; Agriculture, Food Science and Technology (0359); Biology, Microbiology (0410); Biology, Veterinary Science (0778)